Semi-Automated Analysis of Diaphragmatic Motion with Dynamic Magnetic Resonance Imaging in Healthy Controls and Non-Ambulant Subjects with Duchenne Muscular Dystrophy - Bishop, Courtney A.; Ricotti, Valeria; Sinclair, Christopher D. J.; Evans, Matthew R. B.; Butler, Jordan W.; Morrow, Jasper M.; Hanna, Michael G.; Matthews, Paul M.; Yousry, Tarek A.; Muntoni, Francesco; Thornton, John S.; Newbould, Rexford D.; et al. (Frontiers in Neurology, 2018)
Subjects with Duchenne Muscular Dystrophy (DMD) suffer from progressive muscle damage leading to diaphragmatic weakness that ultimately requires ventilation. Emerging treatments have generated interest in better characterising the natural history of respiratory impairment in DMD and responses to therapy. Dynamic (cine) MRI may provide a more sensitive measure of diaphragm function in DMD than the commonly used spirometry. This study presents an analysis pipeline for measuring parameters of diaphragmatic motion from dynamic MRI, and its application to investigate MRI measures of respiratory function in both healthy controls and non-ambulant DMD boys. We scanned thirteen non-ambulant DMD boys and ten age-matched healthy male volunteers at baseline, with a subset (n=10, 10, 8) of the DMD subjects also assessed 3, 6 and 12 months later. Spirometry-derived metrics including forced vital capacity (FVC) were recorded. The MRI-derived measures included the lung cross-sectional area (CSA), the anterior, central and posterior lung lengths in the sagittal imaging plane, and the diaphragm length over the time-course of the dynamic MRI. Regression analyses demonstrated strong linear correlations between lung CSA and the length measures over the respiratory cycle, with a reduction of these correlations in DMD, and diaphragmatic motions that contribute less efficiently to changing lung capacity in DMD. MRI measures of pulmonary function were reduced in DMD, controlling for height differences between the groups: at maximal inhalation, the maximum CSA and the total distance of motion of the diaphragm were 45% and 37% smaller. MRI measures of pulmonary function were correlated with spirometry data, and showed relationships with disease progression surrogates of age and months non-ambulatory, suggesting that they provide clinically meaningful information. Changes in the MRI measures over 12 months were consistent with weakening of diaphragmatic and inter-costal muscles and progressive diaphragm dysfunction. In contrast, longitudinal changes were not seen in conventional spirometry measures during the same period. Dynamic MRI measures of thoracic muscle and pulmonary function are therefore believed to detect meaningful differences between healthy controls and DMD and may be sensitive to changes in function over relatively short periods of follow up in non-ambulant boys with DMD.